2004
DOI: 10.1038/sj.jea.7500414
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the range of children's air pollutant exposure during school bus commutes

Abstract: Real-time and integrated measurements of gaseous and particulate pollutants were conducted inside five conventional diesel school buses, a diesel bus with a particulate trap, and a bus powered by compressed natural gas (CNG) to determine the range of children's exposures during school bus commutes and conditions leading to high exposures. Measurements were made during 24 morning and afternoon commutes on two Los Angeles Unified School District bus routes from South to West Los Angeles, with seven additional ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(53 citation statements)
references
References 19 publications
4
48
1
Order By: Relevance
“…Unfortunately, quantitative ventilation measures were not collected in buses or the automobile and more controlled exposure scenarios may be required for a comprehensive exploration of the effect of window opening on bus and automobile UFP exposures. Nevertheless, it seems likely that closed windows may reduce traffic-related UFP exposures in buses and automobiles, particularly during encounters with large diesel vehicles which can result in substantial increases in cabin pollutants when windows are open Sabin et al, 2005). In this respect, findings from the current study are consistent with those of previous investigations Sabin et al, 2005) as dramatic increases in bus and automobile UFP levels were observed while driving past a coach passenger bus with the windows open (Figure 2b and c).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Unfortunately, quantitative ventilation measures were not collected in buses or the automobile and more controlled exposure scenarios may be required for a comprehensive exploration of the effect of window opening on bus and automobile UFP exposures. Nevertheless, it seems likely that closed windows may reduce traffic-related UFP exposures in buses and automobiles, particularly during encounters with large diesel vehicles which can result in substantial increases in cabin pollutants when windows are open Sabin et al, 2005). In this respect, findings from the current study are consistent with those of previous investigations Sabin et al, 2005) as dramatic increases in bus and automobile UFP levels were observed while driving past a coach passenger bus with the windows open (Figure 2b and c).…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, it seems likely that closed windows may reduce traffic-related UFP exposures in buses and automobiles, particularly during encounters with large diesel vehicles which can result in substantial increases in cabin pollutants when windows are open Sabin et al, 2005). In this respect, findings from the current study are consistent with those of previous investigations Sabin et al, 2005) as dramatic increases in bus and automobile UFP levels were observed while driving past a coach passenger bus with the windows open (Figure 2b and c). However, other studies exploring the effects of window opening on UFP counts in buses or automobiles were not identified.…”
Section: Discussionsupporting
confidence: 90%
“…18 BC, particlebound polycyclic aromatic hydrocarbon (PB-PAH), benzene, and formaldehyde concentrations were all higher as a result of introduction of own exhaust when a school bus's windows were closed. 19 BC, PB-PAH, and benzene levels were higher in a conventional diesel bus than in one using compressed natural gas (CNG), although formaldehyde levels in the CNG bus was higher. 19 The purpose of this study was to identify determinants of in-vehicle PM number and BC concentrations in a transportation microenvironment.…”
Section: Introductionmentioning
confidence: 93%
“…Season, route and ventilation of the vehicles (e.g. open windows) all influence the level of exposure (Lee and Jo 2002;Sabin et al 2005;Zhu et al 2007;Zuurbier et al 2010). The interactions between these factors are likely to contribute to the inconsistencies observed in exposures associated with different transport modes described above.…”
Section: Exposurementioning
confidence: 99%